The mediating effect of teamwork toward organizational readiness for Business Intelligence (BI) implementation - Anjariny, Ahmed H.; Zeki, Akram M.; Abubakar, Adamu (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The growing adaptation to BI is attributed to many factors and its ability to combines corporate data with user-generated content to enhance decision making in improving business environment makes it wide open for future research. Despite some attempts made to address the peculiarities of the factors influencing BI implementation by the findings of many research, yet some controlling variables which influence the factors of successful implementation of BI were not neglected by the research communities. This paper uses the findings of some previous research which indicates that "Teamwork" is a factor which influence organizations' readiness toward BI systems implementation. We use the theory of readiness and investigate the mediating effect of the positive relationship between "Teamwork" and "organizations' readiness toward BI systems implementation". The study was undertaking by quantitative research approach, sample of 200 respondents participated in the study. The result indicates that "Likelihood of a victory" and "Growing optimism about success" had a positive mediating effect on the Teamwork towards organizations' readiness on Implementation of BI systems.